IMMU-09. LOCALLY ADMINISTERED CAR T CELLS DEMONSTRATE MOST FAVORABLE ROUTE OF ADMINISTRATION IN A MODEL OF ATRT. (23rd April 2019) - Theruvath, Johanna; Graef, Claus Moritz; Heitzeneder, Sabine; Majzner, Robbie; Labanieh, Louai; Mackall, Crystal
Abstract: Efficient trafficking and infiltration of CAR T cells to brain tumors is an important determinant of treatment success. Data comparing the route of delivery for CAR-T cells in CNS malignancies is limited, but crucial for successful clinical trial design. We therefore investigated differences in CAR-T cell efficacy, trafficking, toxicity and persistence in intratumoral (IT), intracerebroventricular (ICV) and intravenous (IV) administered CAR-T cells targeting the immune checkpoint B7-H3 in a xenograft model of Atypical teratoid/rhabdoid tumor (ATRT). In order to detect CAR-T cells in vivo we fused a nano-luciferase protein to the CAR construct to simultaneously track tumor growth and CAR-T cell expansion and location. In terms of efficacy, we found that systemic treatment took longer and required a tenfold higher dose to cure the mice compared to locoregional treatment. Tracking of CAR-T cells revealed after 5 days of treatment expansion of CAR-T cells within the tumor of locoregional (IT, ICV) treated mice but not systemic treated mice. Furthermore, 13 days after treatment a significant fraction of locally administered (IT, ICV) CAR-T cells were found in spleen and liver of the mice, demonstrating the migratory potential. No significant differences in CAR-T cell numbers were found in the spleens between the different treatment groups. Regarding toxicity, intravenous administration led to high levels of circulating inflammatory cytokines which were undetectable following local administration. Independent of the route of administration CAR-T cells persisted in brain and spleen. We re-challenged previously treated mice and all groups effectively rejected flank and orthotopic tumors. In summary, local delivery might be favorable in terms of efficacy, trafficking and toxicity, whereas persistence may not depend on the route of delivery. These findings have direct valuable implications for a clinical trial design for CAR-T cell based immunotherapies for ATRT and other CNS malignancies.